1996
DOI: 10.1161/01.hyp.27.5.1073
|View full text |Cite
|
Sign up to set email alerts
|

Pulse Pressure Correlates in Humans With a Proscillaridin A Immunoreactive Compound

Abstract: Endogenous digitalis-like factors in humans are presumably cardenolides and bufadienolides. To test whether bufadienolide-like substances may circulate in human blood, we used antibodies from rabbits against the bufadienolide proscillaridin A to measure the concentration of cross-reacting material in human plasma with an indirect enzyme-linked immunosorbent assay. IgG had an apparent affinity of 2 x 10(-9) mol/L for proscillaridin A. It was specific for bufadienolides and did not cross-react with cardenolides … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
35
0
3

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(39 citation statements)
references
References 22 publications
1
35
0
3
Order By: Relevance
“…Derivatives of cardiotonic steroids with a UV maximum at 250 nm have been described (30), but the molecular mass and the mass fragmentation pattern of inhibitor A is inconsistent with hitherto known cardiotonic steroids; it is also unlikely that the more hydrophilic inhibitor A is a degradation product of ouabain (inhibitor B). Inhibitor A resembles in its retention time and immunological properties the substance whose concentration was found elevated in humans with increased systolic blood pressure (but not diastolic blood pressure) and hence increased pulse pressure (20). Apparently, the type of action of inhibitor A differs from that of ouabain.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Derivatives of cardiotonic steroids with a UV maximum at 250 nm have been described (30), but the molecular mass and the mass fragmentation pattern of inhibitor A is inconsistent with hitherto known cardiotonic steroids; it is also unlikely that the more hydrophilic inhibitor A is a degradation product of ouabain (inhibitor B). Inhibitor A resembles in its retention time and immunological properties the substance whose concentration was found elevated in humans with increased systolic blood pressure (but not diastolic blood pressure) and hence increased pulse pressure (20). Apparently, the type of action of inhibitor A differs from that of ouabain.…”
Section: Discussionmentioning
confidence: 96%
“…Inhibition of 86 RbCl Uptake into Red Blood Cells-This was essentially performed as described previously using a silicon oil centrifugation technique in Eppendorf cups (20,22).…”
Section: Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that mammalian tissues also contain bufadienolide CS. [5][6][7] Bufadienolides were discovered in amphibians and differ from cardenolides in having a 6-membered doubly unsaturated lactone ring. 5 One CS that was purified from human urine by high-performance liquid chromatography mass spectrometrically was identical to an amphibian bufadienolide, marinobufagenin (MBG).…”
mentioning
confidence: 99%
“…Among those are the cardenolides ouabain or its isomer (6 -9), digoxin (10), and the bufadienolides 19-norbufalin (11) and marinobufagenin (12,13). Additional, yet unknown, substances seem to exist (14). Ouabain or its isomer has been shown to be secreted from bovine cortical adrenal cells of the zona glomerulosa in tissue culture (15,16) stimulated with angiotensin II (17).…”
mentioning
confidence: 99%